2005
DOI: 10.1002/smr.313
|View full text |Cite
|
Sign up to set email alerts
|

Design preservation over subsequent releases of a software product: a case study of Baan ERP

Abstract: We present the results of two case studies we conducted at Baan in the Netherlands. At the time of conducting the case studies, Baan was part of Invensys plc. (Baan is now owned by SSA Global Technologies.) In these case studies we investigated how companies identify design erosion and address this in their software, a practice we call 'design preservation'. In this study, we selected two sub-systems in Baan products that had recently been subjected to extensive maintenance activities because they were eroded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Hence, as soon as one of these elements is moved to the subclass, its reference in the superclass is no longer valid, leading to a compiler error. Therefore, these refactorings are all rejected during precondition checking 1 . In this case, our solution is to add new refactorings to the detected refactoring set.…”
Section: B Reification Phase In More Detailmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, as soon as one of these elements is moved to the subclass, its reference in the superclass is no longer valid, leading to a compiler error. Therefore, these refactorings are all rejected during precondition checking 1 . In this case, our solution is to add new refactorings to the detected refactoring set.…”
Section: B Reification Phase In More Detailmentioning
confidence: 99%
“…If the developer ignores the inadequacy of the current design and simply extends the program with the new functionality, the process of design erosion has started. An eroded design results a low quality system in terms of extensibility, flexibility, and maintainability [1].…”
Section: Introductionmentioning
confidence: 99%
“…Problem Statement: During the long-term maintenance of a software system, it is easy for architectural quality to gradually erode as changes are applied to the design and code [38,25,4,13]. This problem is exacerbated when developers making the changes are unaware [30,12,3]of underlying architectural decisions and their rationales.…”
Section: Active Plumblinementioning
confidence: 99%
“…be slowly eroded by ongoing maintenance activities which are inevitably undertaken to correct faults, improve performance or other quality concerns, and to adapt the system in response to changing requirements [38,22]. Even seemingly innocuous changes made to design or code, can often inadvertently lead to degradation of architectural qualities [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that decayed architectures make their systems more prone to defects [14] and that, in some not-so-rare cases, a system architecture and its implementation code must be thrown away because it is too hard to maintain, unless the decay can be stopped before the architecture is completely unworkable [15].…”
Section: Introductionmentioning
confidence: 99%